Building the resilient supply chain. - Christopher, Martin; Peck, Helen (MCB UP Ltd/Emerald Group Publishing Limited, 2004)
In today’s uncertain and turbulent markets, supply chain vulnerability has become an issue of significance for many companies. As supply chains become more complex as a result of global sourcing and the continued trend to ‘leaning-down’, supply chain risk increases. The challenge to business today is to manage and mitigate that risk through creating more resilient supply chains.
Keywords: Risk analysis; Risk management; Supply-chain management